Reports on vascular catheter-associated thromboembolic events in a burn unit - a gap in the literature? - Jarnalo, M; Reis Videira, P; Horta, R (Acta chirurgiae plasticae, 2024)
Indwelling intravascular catheters are important tools in the care of critically ill patients; however, they have an inherent risk of infection or thromboembolic events. Reports on catheter associated thromboembolic events in burn units are rare, despite being well recognized that burn patients bear an increased baseline risk for thromboembolic events. We describe two catheter-associated thromboembolic complications in burn patients in a burn unit and the morbidity associated with these events. Patients with endovascular catheters in burn units may be at increased risk for severe thromboembolic events associated with intravascular catheters, but specific guidelines for prevention and management of these patients are still missing.
Keywords: Burns; Vascular Access Devices; Female; Adult; tromboembolie; dospělí; fatální výsledek; Humans; ženské pohlaví; popálení; mužské pohlaví; popáleninové jednotky; lidé; Male; Fatal Outcome; Thromboembolism; Burn Units; cévní přístupy